Transformation of doped graphite into cluster-encapsulated fullerene cages. Issue 1 (December 2017) - Mulet-Gas, Marc; Abella, Laura; Cerón, Maira; Castro, Edison; Marshall, Alan; Rodríguez-Fortea, Antonio; Echegoyen, Luis; Poblet, Josep; Dunk, Paul
Abstract An ultimate goal in carbon nanoscience is to decipher formation mechanisms of highly ordered systems. Here, we disclose chemical processes that result in formation of high-symmetry clusterfullerenes, which attract interest for use in applications that span biomedicine to molecular electronics. The conversion of doped graphite into a C80 cage is shown to occur through bottom-up self-assembly reactions. Unlike conventional forms of fullerene, the iconic Buckminsterfullerene cage, I h -C60, is entirely avoided in the bottom-up formation mechanism to afford synthesis of group 3-based metallic nitride clusterfullerenes. The effects of structural motifs and cluster–cage interactions on formation of compounds in the solvent-extractable C70 –C100 region are determined by in situ studies of defined clusterfullerenes under typical synthetic conditions. This work establishes the molecular origin and mechanism that underlie formation of unique carbon cage materials, which may be used as a benchmark to guide future nanocarbon explorations. An understanding of how caged carbon materials self-assemble from doped graphite is a long-standing challenge. Here, the authors show that distinct bottom-up processes lead to the synthesis of high-symmetry clusterfullerenes.